2011
DOI: 10.1093/cvr/cvr279
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide enhances microvascular albumin permeability by the caveolae-mediated transcellular pathway

Abstract: AimsCardiac atrial natriuretic peptide (ANP) participates in the maintenance of arterial blood pressure and intravascular volume homeostasis. The hypovolaemic effects of ANP result from coordinated actions in the kidney and systemic microcirculation. Hence, ANP, via its guanylyl cyclase-A (GC-A) receptor and intracellular cyclic GMP as second messenger, stimulates endothelial albumin permeability. Ultimately, this leads to a shift of plasma fluid into interstitial pools. Here we studied the role of caveolae-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 31 publications
5
44
0
1
Order By: Relevance
“…CAV-1 is the main structural component of endothelial caveolae and regulates endothelial transcytosis. Recent studies have shown that CAV-1 plays a key role in the regulation of microvascular endothelial and blood-retinal barrier permeability (42,53). Our results showed that CM from hypoxic trophoblast and HMGB1 increased endothelial cell monolayer permeability and increased CAV-1 protein expression at the same time.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…CAV-1 is the main structural component of endothelial caveolae and regulates endothelial transcytosis. Recent studies have shown that CAV-1 plays a key role in the regulation of microvascular endothelial and blood-retinal barrier permeability (42,53). Our results showed that CM from hypoxic trophoblast and HMGB1 increased endothelial cell monolayer permeability and increased CAV-1 protein expression at the same time.…”
Section: Discussionsupporting
confidence: 63%
“…The HUVECs/MAECs were treated with JEG-3 cells/PMTs CM for an additional 24 h. FITC-BSA uptake of HUVEC/MAECs was performed as previously described with minor modifications (42). FITC-BSA (SigmaAldrich; at a final concentration of 0.5 mg/ml) and Hoechst 33325 (SigmaAldrich; at a final concentration of 1 mg/ml) were added to the cells and incubated for 30 min.…”
Section: Fitc-bsa Huvec Stainingmentioning
confidence: 99%
“…Among nondialysis patients, lung congestion was correlated with the NT-proBNP level [22]. Natriuretic peptides may directly enhance capillary permeability, an effect that may explain the association in addition to filling pressure alone [33]. In this study, we also showed a positive and independent relationship between the number of B-lines and the serum NT-proBNP level in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 61%
“…Both ANP and BNP protected against thrombin-induced barrier dysfunction in the pulmonary microcirculation in a cGMPindependent manner, likely due reduced RhoA activation [22]. Most recently, ANP was shown to promote extravasation of fluorescent albumin from postcapillary venules and to cause arteriolar vasodilation in the mouse cremaster microcirculation [23]. The hyperpermeability effect was prevented in mice with conditional, endothelial deletion of NPR-A as well as in those with deleted caveolin-1, the caveolae scaffold protein.…”
Section: Experimental Evidencementioning
confidence: 97%